2019
DOI: 10.1353/eca.2019.0012
|View full text |Cite
|
Sign up to set email alerts
|

All Medicaid Expansions Are Not Created Equal: The Geography and Targeting of the Affordable Care Act

Abstract: At least one co-author has disclosed a financial relationship of potential relevance for this research. Further information is available online at http://www.nber.org/papers/w26289.ack NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…44 Previous work with diverging results generally assessed changes in ED visits after 1 or 2 years postexpansion, focused their analysis on different states and populations, or reviewed outcomes using different definitions of not-emergent ED visits. 25,31,32 The observed decreases in ED visits concurrently occurred with increases in availability and access to primary care, and more primary care professionals accepting patients with Medicaid coverage to higher Medicaid payment rates. 17,25,43,[45][46][47] Furthermore, decreases in Medicaid expansion states were concentrated in conditions that were less-emergent or not medically emergent, suggesting that access to preventive services could have substituted ED visits, improved health, and stabilized health conditions, which rendered ED use not necessary.…”
Section: Expansion States Nonexpansion Statesmentioning
confidence: 99%
“…44 Previous work with diverging results generally assessed changes in ED visits after 1 or 2 years postexpansion, focused their analysis on different states and populations, or reviewed outcomes using different definitions of not-emergent ED visits. 25,31,32 The observed decreases in ED visits concurrently occurred with increases in availability and access to primary care, and more primary care professionals accepting patients with Medicaid coverage to higher Medicaid payment rates. 17,25,43,[45][46][47] Furthermore, decreases in Medicaid expansion states were concentrated in conditions that were less-emergent or not medically emergent, suggesting that access to preventive services could have substituted ED visits, improved health, and stabilized health conditions, which rendered ED use not necessary.…”
Section: Expansion States Nonexpansion Statesmentioning
confidence: 99%
“…These results highlight the importance of understanding how the effects of public insurance programs differ by locality and race and ethnicity when assessing their potential to advance health equity. 42 Our findings also suggest that expanding Medicare may be a viable means to reduce racial and ethnic disparities and advance health equity by closing coverage gaps across the US.…”
Section: Hispanic Respondentsmentioning
confidence: 58%
“…Although Giannouchos et al 3 found encouraging patterns of ED use, other studies have found the opposite. In particular, a 2019 study by Garthwaite et al, 8 which also used Healthcare Cost and Utilization Project data, but included 20 states and all ED visits (both outpatient ED visits as well as those leading to inpatient admission), found that ED use for deferrable conditions increased in expansion states relative to nonexpansion states, whereas those for nondeferrable conditions did not. The authors defined deferrable conditions as those that a panel of physicians believed were likely to be at the patient's discretion, and nondeferrable conditions as those that were truly emergent and not likely to be discretionary.…”
Section: + Related Articlementioning
confidence: 99%